Designing the ECO-ITERATE Framework for Local Socio-Ecological Problem-Based Natural and Social Sciences Learning: A Systematic Integrative Review - Wahyu Ramdhani; Wasino Wasino; Muzakki Basori (Proceedings of International Conference on Science, Education, and Technology, 2026)
Elementary Natural and Social Sciences learning requires a pedagogical design that connects scientific concepts, social practices, local environmental conditions, evidence, and responsible action. Previous studies commonly examine scientific literacy, environmental literacy, local wisdom, problem-based learning, and socio-scientific issues as separate strands. This study integrates those strands and designs the ECO-ITERATE framework for elementary learning. A focused systematic integrative review was conducted on 13 peer-reviewed studies published from 2020 to June 2026, supported by the Indonesian IPAS curriculum, the PISA 2025 assessment framework, and PRISMA 2020 reporting principles. Sources were selected through relevance, methodological clarity, outcome relevance, and bibliographic verification criteria, then coded by educational level, local issue, learning approach, inquiry activity, literacy outcome, and evidence directness. The synthesis produced five design principles: local-problem anchoring; integration of scientific, social, environmental, data, and civic literacy; scaffolded evidence-based inquiry; evaluation linked with reflection and collective action; and iterative transfer and redesign. These principles were organized into ten stages: Engage, Connect, Observe, Investigate, Transform, Evaluate, Reflect, Act, Transfer, and Extend. ECO-ITERATE is proposed as a conceptually grounded, classroom-oriented framework that still requires expert validation, practicality testing, limited classroom trials, and comparative effectiveness research